ANALISIS PERILAKU LESS-INTERACTION SISWA DALAM PROSES PEMBELAJARAN KELAS - Salwa Najmira; Naila Insani; Levina Amelia Maharani; Rizty Azzahra Sastradipura; Deti Rostika (STKIP Subang, 2023)
ABSTRACT This research aims to analyze students' less-interaction behavior in the classroom learning process. Less-interaction refers to the level of student participation and involvement that is less in active interaction with learning materials, teachers, and fellow classmates. This research was conducted using academic literature as well as related primary and secondary sources. The results of the research show that there are variations in the level of students' lack of interaction, which is reflected in the lack of active participation in class discussions, inactivity in group assignments, and lack of initiative in seeking understanding. addition. In addition, interpersonal communication between students is also limited, reducing opportunities for the exchange of ideas and mutual understanding. Factors that contribute to less-interaction behavior include students' discomfort in speaking in public, lack of motivation towards learning material, as well as technical obstacles that arise. related to the use of technology in learning. Some students may feel uncomfortable or lack confidence in speaking in front of the class, while others may prefer to learn independently without much social interaction. The implications of these findings highlight the need for learning strategies that can increase participation and engagement students, such as the use of interactive teaching methods, increasing social support, and developing student communication skills. In addition, implementing an approach that takes into account individual learning styles and minimizes technical barriers can be effective steps to overcome students' less-interaction behavior. These findings have important implications for designing more inclusive and interactive learning. Teachers can develop learning strategies that encourage active participation, provide extra support for students who tend to lack interaction, and create a classroom environment that supports collaboration. Thus, increasing student interaction can increase learning effectiveness and create a more positive learning experience. ABSTRAK Penelitian ini bertujuan untuk menganalisis perilaku less-interaction siswa dalam proses pembelajaran kelas. Less-interaction merujuk pada tingkat partisipasi dan keterlibatan siswa yang kurang dalam interaksi aktif dengan materi pembelajaran, guru, dan rekan sekelas. Penelitian ini dilakukan dengan menggunakan literatur akademis serta sumber-sumber primer dan sekunder terkait.Hasil penelitian menunjukkan bahwa terdapat variasi dalam tingkat less-interaction siswa, yang tercermin dalam kurangnya partisipasi aktif dalam diskusi kelas, ketidakaktifan dalam tugas kelompok, dan minimnya inisiatif dalam mencari pemahaman tambahan. Selain itu, komunikasi interpersonal antara siswa juga terbatas, mengurangi peluang untuk pertukaran ide dan pemahaman bersama.Faktor-faktor yang berkontribusi terhadap perilaku less-interaction meliputi ketidaknyamanan siswa dalam berbicara di depan umum, kurangnya motivasi terhadap materi pembelajaran, serta kendala-kendala teknis yang terkait dengan penggunaan teknologi dalam pembelajaran.Beberapa siswa mungkin merasa tidak nyaman atau kurang percaya diri dalam berbicara di depan kelas, sementara yang lain mungkin lebih suka belajar secara mandiri tanpa banyak interaksi sosial.Implikasi temuan ini menyoroti perlunya strategi pembelajaran yang dapat meningkatkan partisipasi dan keterlibatan siswa, seperti penggunaan metode pengajaran yang interaktif, peningkatan dukungan sosial, dan pengembangan keterampilan komunikasi siswa. Selain itu, penerapan pendekatan yang memperhitungkan gaya belajar individu dan meminimalkan hambatan teknis dapat menjadi langkah-langkah yang efektif untuk mengatasi perilaku less-interaction siswa. Penemuan ini memiliki implikasi penting untuk perancangan pembelajaran yang lebih inklusif dan interaktif. Guru dapat mengembangkan strategi pembelajaran yang mendorong partisipasi aktif, memberikan dukungan ekstra bagi siswa yang cenderung less-interaction, dan menciptakan lingkungan kelas yang mendukung kolaborasi. Dengan demikian, peningkatan interaksi siswa dapat meningkatkan efektivitas pembelajaran dan menciptakan pengalaman pembelajaran yang lebih positif.